Electrochemistry of Semiconductors and Electronics - Processes and Devices - McHardy, John (Noyes Publications, 2011)
This book covers possible electrochemical avenues towards the goals of achieving greater semiconductor purity, crystal uniformity, and circuit density, and thus, faster more compact electronic devices.